Livestock marketing in six auctions in Costa Rica from 2007 to 2013. (UNED Research Journal, 2015)
Changes in sale and purchase of livestock allow identification of the type of animal that producers want, variations in supply and demand, and their impact on price. To understand this for Costa Rica, we analyzed the number and sales prices of auctioned livestock from 2007 to 2013. Information provided by the auctions included location, date, number of animals, sex, weight, marketing category and price. Auction was a highly significant variable (p
Keywords: Cow; bulls; selling price; cattle; male/female relationship; sales category.